Tacrolimus treatment in women with repeated implantation failures - Koji Nakagawa; Rikikazu Sugiyama (Reproductive Medicine and Biology)
Abstract Background Tacrolimus is an immunosuppressive drug that works as a calcineurin inhibitor to improve the reproductive outcomes for women who have experienced multiple implantation failures (RIF) and show elevated type 1 helper T (Th1)/Th2 cell ratios. Methods In the first part of this review, we indicate how we re‐evaluated the cut‐off index for selecting the participants in a tacrolimus regimen via transferred euploid blastocysts. In the second part, we cite cases where tacrolimus has improved the live birth rate for women who have experienced recurrent pregnancy losses (PRL) and we introduce the utility of tacrolimus treatment to prevent obstetrical complications. Main Findings After reconsideration of the cut‐off index (Th1/Th2 ≥ 11.8), however, the pregnancy rates of women with tacrolimus were significantly higher than those of women without tacrolimus. The PRL women treated with tacrolimus showed significantly lower rates of biochemical pregnancy, but higher live‐birth rates compared with women who were not treated with tacrolimus. Moreover, prior severe obstetrical complications could be controlled via the administration of tacrolimus during pregnancy. Conclusion Tacrolimus has become indispensable in the field of solid‐organ transplantation, and in the near future, it should become an essential agent in the reproductive field, as well.